Honey-bees, court ladies, and beekeeping in Java before 1500 CE - Jákl, JiŘí (Wacana, Journal of the Humanities of Indonesia, 2022)
People have been interacting with bees in the Indo-Malay world for thousands of years. Though the practice of robbing bees of honey and wax is relatively well-documented, we know very little about the early history of beekeeping in Southeast Asia. In this study I will use Old Javanese evidence to demonstrate that providing honey bees with artificial cavities was a practice known in Java at least by the twelfth century CE, several centuries earlier than suggested by the historians of beekeeping. In the second part of my contribution I will discuss in detail an intriguing passage in the Sumanasāntaka, a court poem composed in the early thirteenth century CE, in which a literary motif of the “marriage by choice“ (swayamwara) of Princess Indumatī is based on the image and structure of beehive. The idea that a bee-colony is ruled by the “queen“ rather than the “king“ was not widely known in pre-modern world, and the Sumanasāntaka suggests that pre-Islamic Javanese were good observers of nature.